Optical and Structural Properties of Cobalt Nanoparticles Synthesized by Laser Ablation - Jasim , Awatif Sabir; Aadim , Kadhim A.; Rashid , Sahar Naji (Iraqi Journal of Science, 2022)
Pulsed laser ablation in liquid (PLAL) technique can produce high purity nanoparticles, it is a top-down physical method based on the principle of dividing metal ion bulk precursors into metal atoms, this method was used in this work to synthesis cobalt nanoparticals (CoPNs) with the use of Nd: YAG laser with two wavelengths (355 nm) and (532 nm) at energies (500 mJ) and (600 mJ) respectively, with number of pulses (1000,1100, 1200, 1300, and 1400) for each wavelength. The properties of the prepared nanoparticles were studied by UV-Vis, XRD, SEM with EDX, AFM, and FTIR analysis and then its antibacterial activity was studied by applying it on two types of bacteria with gram-positive (Staphylococcus aureus, Streptococcus mutans) and two gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa) isolated from the oral cavity. The findings showed that CoNPs prepared using the PLAL approach have antibacterial activity and could be employed to kill hazardous and pathogenic bacteria.